Presence of Histoplasma capsulatum in faeces of homing pigeons and rock pigeons in Lima, Peru - Arias Guerrero, Yurie (2017)
The fungus Histoplasma capsulatum is the causative agent of histoplasmosis, disease of public health importance. The aim of this study was to determine its presence in faeces of domestic pigeons (Columba livia) in the city of Lima, Peru. Faecal samples (n=245) were collected, processed and cultivated in Sabouraud agar at 37 and 28 °C for 2 to 4 weeks approximately. The colonies were identified by macroscopic and microscopic characteristics. Only 0.41% (1/245) of samples were positive to H. capsulatum, while the beta-pert (@Risk) stochastic simulation showed a minimum prevalence of 0.369% and a maximum prevalence of 0.451%.